Perbandingan Metode Trend Projection dan Triple Exponential Smoothing Peramalan Jumlah Kebutuhan Vaksin pada Balita - Priyamita, Adinda; Triase, Triase (Program Studi Teknik Informatika Universitas Pamulang, 2024)
The demand for vaccines for toddlers at the Rasmi Pekan Bahorok Clinic is currently considered not optimal. There is still a tendency to buy vaccines excessively, which results in the accumulation of vaccine stocks in storage. This increases the risk that the vaccine will become ineffective because it has passed its expiration date, while if the number of immunization vaccines is reduced, it could result in a shortage of vaccines for children. The lack of a proper calculation process to determine vaccine needs often results in errors in estimating the amount needed. As a result, vaccine stock at the Rasmi Pekan Bahorok Clinic is currently unstable. This situation is a problem at the clinic, so it is necessary to implement a forecasting system to calculate the vaccine stock that will be available each following month. To deal with this problem, it is necessary to forecast or predict to understand the situation in the future using past data. This can help in managing vaccine stocks to remain stable and optimize company operations. Therefore, a system was developed that can predict the number of vaccines needed. This system is expected to assist in decision making to resolve problems that arise. The methods used in this information system include the Trend Projection method and the Triple Exponential Smoothing method.